Microbiological Study of Diabetic Foot Ulcer - Mohammuddunnobi, -; Jahan, Tasnuva; Amin, Abdullah Al (Anwer Khan Modern Medical College Journal, 2019)
Background: Diabetic foot is one of the most feared complications of diabetes and is the leading cause of hospitalization in diabetic patients. Limb-threatening diabetic infections are usually polymicrobial involving multiple aerobic and anaerobic organisms. Methodology: The present study was a cross sectional study, conducted in the department of surgery and microbiology at BIRDEM General Hospital, Dhaka, over a period of 9 months during January 2017- September' 2017. The study included a total of 77 adult patients of clinically diagnosed diabetic foot patients presenting to outpatient department and emergency ward. The standard case definition of diabetic foot is 'any pathology occurring in the foot of a patient suffering from diabetes mellitus or as a result of long term complication of diabetes mellitus'. Results: Majority 17(22.1%) patients had Klebsiella pneumonia, 14(18.2%) had Pseudomonas aeruginosa, 11(14.3%) had Staphylococcus aureus, 10(13.0%) had Escherichia coli, 6(7.8%) had Coagulase-negative staphylococci and 8(10.4%) had Providencia spp. In Escherichia coli 100% sensitivity to imipenem, 70% to amoxicillin-clavulanic acid, amikacin, piperacillin-tazobactam. In Coagulasenegative Staphylococci 83.3% sensitivity to tetracycline, 66.7% to ceftriaxone. In Proteus mirabilis 100% sensitivity to tetracycline, amikacin, ceftriaxone, imipenem, piperacillin-tazobactam. In Enterococcus spp.75.0% sensitivity to tetracycline. In Citrobacter spp. 100% sensitivity to imipenem. Conclusion: Common organism found in diabetic foot ulcer patients were Klebsiella pneumonia, Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Coagulase-negative staphylococci and Providencia spp. In tetracycline, amikacin, ceftriaxone, imipenem, piperacillin-tazobactam was 100% sensitive in Proteus mirabilis and only imipenem found in Escherichia coli and Citrobacter spp. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 50-55